2008
DOI: 10.1017/s1751731108002632
|View full text |Cite
|
Sign up to set email alerts
|

Use of gene expression data for predicting continuous phenotypes for animal production and breeding

Abstract: Traits such as disease resistance are costly to evaluate and slow to improve using current methods. Analysis of gene expression profiles (e.g. DNA microarrays) has potential for predicting such phenotypes and has been used in an analogous way to classify cancer types in human patients. However, doubts have been raised regarding the use of classification methods with microarray data for this purpose. Here we propose a method using random regression with cross validation, which accounts for the distribution of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Apart from the use of gene expression profiles to better understand the function and regulation of genes, Robinson, Goddard and Hayes (2008) have proposed the use of gene expression profiles in indirect selection for disease resistance. The concept is that certain cells (e.g., macrophages or leucocytes) will respond to the disease agent, and the resulting cascades of gene expression changes in these cells could potentially differ between animals that are able to resist versus those that are more susceptible to the disease.…”
Section: Genomic Information In Selection For Improved Disease Resistmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the use of gene expression profiles to better understand the function and regulation of genes, Robinson, Goddard and Hayes (2008) have proposed the use of gene expression profiles in indirect selection for disease resistance. The concept is that certain cells (e.g., macrophages or leucocytes) will respond to the disease agent, and the resulting cascades of gene expression changes in these cells could potentially differ between animals that are able to resist versus those that are more susceptible to the disease.…”
Section: Genomic Information In Selection For Improved Disease Resistmentioning
confidence: 99%
“…The use as a selection tool assumes that a method of eliciting a gene expression response from breeding candidates is available, e.g., by challenging cells derived from these individuals to disease. Robinson et al (2008) evaluated a method for formulating prediction equations using random regression with cross‐validation on a set of gene expression data from breast cancer patients, and found a moderate correlation between the predicted and the actual phenotype (0.32±0.06). Based on simulations using gene expression data in a selective breeding programme for Atlantic salmon, Robinson and Hayes (2008) found that use of such data in combination with sib challenge testing would improve both the accuracy and intensity of selection and would thus speed up genetic gain for disease resistance.…”
Section: Genomic Information In Selection For Improved Disease Resistmentioning
confidence: 99%
“…The eQTL are used to develop biomarkers to monitor, diagnose and predict phenotypes (see below). While it is possible to use eQTL for the selection of animals [92], at present, to the best of our knowledge, this is not practiced yet by breeding companies. The main reason for this may be that the structure of the breeding schemes is not optimized for using this type of data, together with the unfamiliarity of the breeding companies with the potential of the eQTL and unavailability of data in the breeding lines.…”
Section: Functional Genomementioning
confidence: 99%
“…Interestingly, the genes for two histone proteins (HH7(1) and LD1 (8)) were expressed at high levels in the resistant groups ( Table 2). Although histones mainly serve as structural components of nucleosomes, but they can also act as antimicrobial agents [45].…”
Section: Differentially Expressed Genes Between Resistant and Susceptmentioning
confidence: 99%